THE IMPLEMENTATION OF PRESIDENT AND VICE PRESIDENT ELECTION IN PEOPLE’S CONSULTATIVE ASSEMBLY (MPR) (A CONSTITUTIONAL LAW STUDY) - Bruaharja, Isman; Primayanti, Andi Dewi (Tadulako University, 2021)
The People’s consultative Assembly is the highest state institution that has undergone a change in the constitutional structure after the amandements to the 1945 Constitution, changes to the MPR are very clearly seen in the first to the fourth amandements to the 1945 Constitution. Before the amandement to the 1945 Constitusion , The MPR as the highest state institusion was given unlimited powers,and MPR is the one that has the authority to enact the 1945 Constitution,GBHN,Appoint the president and vice president in a accordance with the provisions of article 3 paragraph 1 of the 1945 Constitution before the amandement the MPR stipulates the constitution and the GBHN. The existence of the MPR at this time is indeed a high state institution The MPR stikk existence has no position as no longer as the highest state institution and the big question is whether its existence is the absolute holder of the people’s sovereignty